A Preliminary Study of Intimate Partner Violence Among Nepali Women in the United States - Thapa-Oli, S.; Dulal, H. B.; Baba, Y. (2012)
Although there is a growing number of studies on intimate partner violence ( IPV) in U. S. South Asian communities, the examination of IPV among Nepali women in the United States is still in the initial stage. The purpose of this study was to assess the prevalence of and vulnerabilities to IPV among 45 Nepali immigrant women residing in the New York metropolitan area. The findings demonstrated that 75.6% of women had been verbally insulted by their current partners, and 62.2% had to seek permission from their partners to go to their friends' or relatives' houses.